2021
DOI: 10.1101/2021.04.15.440067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapalogs downmodulate intrinsic immunity and promote cell entry of SARS-CoV-2

Abstract: Infection by SARS-CoV-2 generally causes mild symptoms but can lead to severe disease and death in certain populations, including the immunocompromised. Drug repurposing efforts are underway to identify compounds that interfere with SARS-CoV-2 replication or the immunopathology it can elicit. Rapamycin is among those being currently tested in clinical trials for impacts on COVID-19 severity. While rapamycin and rapamycin analogs (rapalogs) are FDA-approved for use as mTOR inhibitors in multiple clinical settin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 139 publications
(233 reference statements)
0
9
0
2
Order By: Relevance
“…TMT labeling-based proteomics analysis was performed as previously described ( Shi et al, 2021 ). In brief, cell pellets were produced in duplicate from cell lines and lysed in 50 mM HEPES, pH 8.0 and 8M urea followed by sonication.…”
Section: Methodsmentioning
confidence: 99%
“…TMT labeling-based proteomics analysis was performed as previously described ( Shi et al, 2021 ). In brief, cell pellets were produced in duplicate from cell lines and lysed in 50 mM HEPES, pH 8.0 and 8M urea followed by sonication.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a cohort study in a TSC clinic in Italy revealed the similar trend: those patients receiving treatment with Rapalogs were found to have better clinical outcomes in COVID-19 [133]. However, in tissue culture and in immunologically naive animals, there is evidence that exposure to Rapalogs enhances vulnerability to SARS-CoV-2 infection [134]. Such controversial results have raised questions about whether Rapalogs can be used as a treatment for Covid-19.…”
Section: Agents Targeting the Mtorc1-autophagy-pathwaymentioning
confidence: 99%
“…[27], хроническая активация mTORC1 способствует повышению экспрессии генов ACE2 и TMPRSS2 в пневмоцитах II типа, что делает их более уязвимыми к проникновению вируса SARS-CoV-2. С другой стороны, блокаторы mTORС1 могут самостоятельно способствовать проникновению вируса SARS-CoV-2 в эпителиальные клетки верхних дыхательных путей и легких посредством уменьшения активности трансмембранных белков, активируемых интерфероном I типа [28]. Кроме этого, у женщин с мутациями в гене TSC2 одной из характерных черт является повышенная выработка провоспалительных цитокинов в легких, что предрасполагает к формированию в них воспалительного фенотипа [29].…”
Section: 2020 начата инотропная поддержка с первых суток пребывания в...unclassified
“…Рапамицин in vitro уменьшает активацию генов интерферонового каскада [41], приводит к поляризации макрофагов преимущественно по провоспалительному М1-варианту [42], снижает экспрессию противовоспалительного цитокина интерлейкина 10 (ИЛ10), стимулирует активацию тканевого фактора и фактора некроза опухоли α (ФНОα) [43]. Блокаторы mTORС1 могут способствовать проник-новению вируса SARS-CoV-2 в эпителиальные клетки верхних дыхательных путей и легких посредством уменьшения активности трансмембранных белков, активируемых интерфероном I типа [28]. Важно отметить, что дополнительное к препаратам -блокаторам mTORC1 воздействие на иммунный ответ может оказывать и сам инфекционный агент.…”
Section: 2020 начата инотропная поддержка с первых суток пребывания в...unclassified